2006
DOI: 10.1186/1471-2164-7-226
|View full text |Cite
|
Sign up to set email alerts
|

High degree of conservancy among secreted salivary gland proteins from two geographically distant Phlebotomus duboscqi sandflies populations (Mali and Kenya)

Abstract: Background: Salivary proteins from sandflies are potential targets for exploitation as vaccines to control Leishmania infection; in this work we tested the hypothesis that salivary proteins from geographically distant Phlebotomus duboscqi sandfly populations are highly divergent due to the pressure exerted by the host immune response. Salivary gland cDNA libraries were prepared from wild-caught P. duboscqi from Mali and recently colonised flies of the same species from Kenya.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 51 publications
3
78
0
Order By: Relevance
“…24 They are also very similar in sequence to the SP15 protein of the related sand fly P papatasi (≈65% amino acid identity; Figure I in the online-only Data Supplement). 25 Proteomic analysis has shown this group to be the most abundant group of proteins in the saliva of P duboscqi .…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…24 They are also very similar in sequence to the SP15 protein of the related sand fly P papatasi (≈65% amino acid identity; Figure I in the online-only Data Supplement). 25 Proteomic analysis has shown this group to be the most abundant group of proteins in the saliva of P duboscqi .…”
Section: Resultsmentioning
confidence: 73%
“…25 Proteomic analysis has shown this group to be the most abundant group of proteins in the saliva of P duboscqi . 24 …”
Section: Resultsmentioning
confidence: 99%
“…maturation. Classical genetics studies have shown that the genetics of red rice is controlled by two loci, namely Rd and Rc (Kinoshita, 1995;Kato et al, 2006). The pericarp is brown-pigmented when Rc is present alone and is colorless when Rd is present alone; however, the presence of both Rd and Rc impart red color to the pericarp.…”
Section: Introductionmentioning
confidence: 99%
“…By using transcriptomic analysis, the saliva of the wild versus the colonized sand flies, collected from different geographical localities, have been compared. The obtained results indicate high levels of homology between the saliva transcripts from different sand fly groups [85]. Further proteomics analyses are required to illuminate such differences.…”
Section: New Approaches To the Vaccine Developmentmentioning
confidence: 99%